1995
DOI: 10.1097/00000658-199504000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Gastrogastric Fistulas A Complication of Divided Gastric Bypass Surgery

Abstract: ObjectiveThis report warns that gastrogastric fistulas may follow the division of the stomach in bariatric surgery. Summary Background DataAlthough surgery is the most effective therapy for morbid obesity, the procedures are still undergoing evolution. One of the key elements in bariatric surgery is the partition of the stomach to develop a much smaller reservoir. The partition has been done with single layers of staples with almost universal failure and with double layers of staples with a failure rate of 11.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(58 citation statements)
references
References 7 publications
1
53
0
4
Order By: Relevance
“…GGF continue to occur with a reported incidence of up to 6%. 10,12,13 We have previously reported a 1.2% incidence of GGF in our series of patients after divided LRYGB. 14 The optimal management of GGF remains controversial, and reports of surgical treatment of this complication are infrequent.…”
mentioning
confidence: 58%
“…GGF continue to occur with a reported incidence of up to 6%. 10,12,13 We have previously reported a 1.2% incidence of GGF in our series of patients after divided LRYGB. 14 The optimal management of GGF remains controversial, and reports of surgical treatment of this complication are infrequent.…”
mentioning
confidence: 58%
“…Staple line dehiscence is seen primarily when the pouch is created by an undivided staple line through the proximal stomach [4,5,8]. Clearly, once a connection between the gastric remnant and the pouch is established, the jejunal mucosa is exposed to a greater volume of low-pH fluid.…”
Section: Gastric Acidmentioning
confidence: 99%
“…In 1995, Cucchi et al [50] observed an incidence rate of 6%. The high incidence might be a result of the stapling devices used in the former days, which did not divide the gastric tissue.…”
Section: Resultsmentioning
confidence: 99%